Iron isotopes as an ore‐fluid tracer: Case study of Qingchengzi Pb‐Zn‐Au(‐Ag) orefield in Liaoning, NE China. Issue 4 (17th June 2021) - Li, Dedong; Wang, Yuwang; Wang, Jingbin; Lai, Chunkit; Qiu, Jinzhu; Wang, Wei; Li, Shenghui; Zhang, Zhichao
Abstract: The Qingchengzi Pb‐Zn‐Au (‐Ag) orefield (eastern Liaoning province, NE China) is located in the northeastern margin of the North China Craton. The unconventional Fe isotopes of pyrites were analyzed to unravel the ore‐material source and migration pathway of the ore fluids. Pyrite samples of ores and wallrocks from various deposits in the orefield were collected and the solutions were analyzed by MC‐ICP‐MS. The results show that most pyrite samples contain heavier Fe isotopes than the international pyrite standard IRMM‐014. Within a particular deposit, Fe isotopes become lighter with depth. For example, the pyrite δ 56 Fe values drop from 0.216 0.408‰ (150‐m level) to −0.284 to −0.132‰ (210‐m level) at the Zhenzigou deposit. Gold deposits in the orefield also have similar features: At Baiyun (Huangdianzi), the pyrite δ 56 Fe values (0.394 0.627‰) of the silicic‐/potassic‐altered rock‐type ore (130‐m level) are significantly higher than that (0.359‰) of the quartz vein‐type ore (440‐m level). The lamprophyre δ 56 Fe values from different deposits are largely similar (0.040 0.024‰), whereas those in the wallrocks vary considerably (0.144 1.238‰). Compiling the pyrite δ 56 Fe values from many important sedimentary/metamorphic rock units in the region and magmatic‐hydrothermal deposits around the world, we concluded that the Qingchengzi Pb‐Zn‐Au(‐Ag) deposits belong to intrusion‐related magmatic‐hydrothermal type. The spatial fluid isotope variation pattern, and the fact that early‐formed sulfides have lighter isotopes than later ones, suggest that the Qingchengzi ore fluids may have originated from Zhenzigou‐Diannan (hydrothermal center) and outflown to Xiaotongjiapuzi, Gujiapuzi‐Baiyun and Erdao‐Xiquegou areas. The spatial fluid isotope variation pattern also suggests another possible hydrothermal center at Baiyun‐Gujiapuzi. The ability to identify hydrothermal center(s) and delineate fluid migration pathways suggests that pyrite Fe isotopes can serve as a tool for precious and base metals prospecting. Abstract : Most Qingchengzi pyrite has heavier Fe isotopes than the pyrite standard IRMM‐014. All the Fe isotope data fall into the magmatic‐hydrothermal mineralization field. Fe isotopes become lighter with depth, implying late high‐d56Fe ore‐fluid ascent. Fe isotopes‐inferred ore‐fluid pathway coincides spatially with local Pb‐Zn‐Au deposits.